173k views
16 votes
P1 = (1,5). P2 = (x,2) .p1p2=5 ​

1 Answer

4 votes


\qquad\qquad\huge\underline{{\sf Answer}}♨

Let's use distance formula :


\qquad \sf  \dashrightarrow \: \sqrt{(x - 1) {}^(2) + (2 - 5) {}^(2) } = 5


\qquad \sf  \dashrightarrow \: {(x - 1) {}^(2) + ( - 3) {}^(2) } = 5 {}^(2)


\qquad \sf  \dashrightarrow \:(x - 1) {}^(2) + 9 = 25


\qquad \sf  \dashrightarrow \:(x - 1) {}^(2) = 16


\qquad \sf  \dashrightarrow \:(x - 1) = 16


\qquad \sf  \dashrightarrow \:(x - 1) = \pm4


\qquad \sf  \dashrightarrow \:x = 5 \: \: or \: \: - 3

User Ilsa
by
4.7k points